PEMANFAATAN KACANG TANAH UNTUK PRODUKSI SELAI KACANG COKLAT SEHAT BERGIZI - Rahmawati, Rahmawati; A. Muflihunna; Sukmawati (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2024)
Peanuts are one of the agricultural products developed in Borisallo village. Peanuts are rich in fat (non-cholesterol), protein, carbohydrates, vitamins E, A, K and B-complex, minerals Fe, F, Ca, contain lecithin and choline, amino acids lysine, methionine and threonine, the fat content is 50% unsaturated fat, contains phytosterols that help the absorption of cholesterol and has a low glycemic index value because of its high fiber content. This activity aims to teach partners how to process peanuts into healthy and nutritious chocolate peanut butter. This activity is carried out by providing a pre-test questionnaire, followed by providing materials and training. PkM partners are given material about the nutrients contained in peanuts and their health benefits and training on how to process peanuts into healthy and nutritious chocolate peanut butter. Based on the results of the pre- and post-material questionnaires, the results obtained were an increase in partner understanding of ......%. It can be concluded that the implementation of PkM in Borisallo village, Parangloe district, Gowa Regency provides benefits for partners in utilizing peanut agricultural products into healthy, nutritious and popular food products. Keywords : Borisallo; peanut, chocolate peanut butter